Pengembangan Multimedia Interaktif untuk Meningkatkan Kemampuan Pemecahan Masalah dan Self Confidence Siswa - Azzahra, Luthfia; Nurhanurawati, Nurhanurawati; Firdaus, Rangga (Mandalika Mathematics and Educations Journal, 2025)
The lack of precise learning media causes students to have low problem-solving ability and Self Confidence. This research aims to produce interactive multimedia that is valid, practical, and effective in improving students’ problem-solving skills and Self Confidence. The development of this product uses ADDIE’s research procedure. The trial was conducted on linear regression material in class XI of SMA Negeri 4 Kotabumi for the 2024/2025 school year. The data collection techniques used were interviews in preliminary research, tests, and questionnaires. Data analysis techniques include validity tests, practicality tests, and effectiveness tests using t-tests and proportions tests. The development results show that interactive multimedia is categorized as valid and practical, with a material validation score of 85% and an average media score of 88%. The average response score of teachers was 94.21% and students 92.61%, so the product was declared very practical. Based on the t-test, there was a difference in post-test scores between students who used interactive multimedia and those who did not. The results of the proportion test showed that the problem-solving ability and Self Confidence of students who used interactive multimedia reached more than 60% completeness. In conclusion, interactive multimedia meets valid, practical, and effective criteria to improve students’ problem-solving skills and Self Confidence.